SEVENTH GRADE SCIENCE AND TECHNOLOGY CURRICULUM MODULATION: ORIGINAL MEANINGS/ANALOGIES BY TEACHERS - Abdullah AYDIN (Fırat University, 2019)
The purpose of this study is to identify how frequently teachers use the analogies, included in the 7th Grade Science and Technology Textbook, about the concepts “urinary system, nerves system, screw and inclined plane, series circuit, electric circuit, symbols for elements, the electron’s orbit around the nucleus, layer (energy level), electron configuration at layers (energy levels), the electron’s configurations, the area in which electrons orbit around the nucleus, chemical bond”, all of which are found in the 7th Grade Science and Technology Curriculum, and to determine whether they assign original meanings to these concepts and use other analogies than the ones included in the textbook. The study was based on survey and document analysis, two qualitative study methods. The sample was comprised of 100 Science and Technology teachers working for 53 different public secondary schools randomly chosen from Bagcilar, Istanbul. For data collection purposes, a “Teachers’ Questionnaire” was designed to reveal the analogies used on the basis of the textbook. A three-point Likert type scale, the questionnaire contained 11 sample analogies from the textbook. Moreover, 11 open-ended questions were addressed to the participants about the analogies they used other than the ones included in the textbook. The findings suggest that the teachers mostly used analogies about the concept “screw and inclined plane” whereas they used few of the sample analogies about “layers (energy levels)”. In addition, it was observed that they assigned original meanings to these concepts and used other analogies than the ones included in the textbook. However, this was not the case for the concepts “electric circuit” and “symbols for elements”. Therefore, it can be recommended that these original meanings / analogies should not be ignored while the curriculum is revised.